Distribution of the genus Tityus Koch, 1836 (Scorpiones: Buthidae) in the city of La Plata (Argentina) - Giambelluca, Luis Alberto (2021)
In the city of La Plata occurs the genus Tityus with records dating back to 1943. The territorial distribution of the genus Tityus in this city and its expansion was studied based on inquiries received at the CEPAVE Arachnology Laboratory from individuals and public and private institutions. 189 inquiries were received from 2005 to 2020. The QGIS program was used to geolocate each scorpion with urban layout layers and storm drains. For the spatial analysis of distribution, a home range of one hectare per individual was considered to calculate the area and in the cases of areas of overlapping influences during the same year, the area was considered as their union. The genus Tityus in the city of La Plata is represented by the species T. carrilloi and T. confluens, both of health interest and of synanthropic habits, which occupy two different well-defined areas. The analysis of the independent dispersion in the two zones would indicate that they could use the drains to disperse, and since they are unconnected there would be no flow of scorpions between both zones. The colonization of these species in the study area was strengthened for T. confluens as of 2005 and for T. carrilloi as of 2011. The highest records are in the warm months, from January to April, the latter being of higher value. September is the only month without complaints. The expansion rate calculated was 4.42 ha/year.